(untitled) (Economic and Political Thought, 2023)
The process of building networks for the provision of telecommunications services using 5G technology has been ongoing for several years, and will be used in various sectors of the newest industries, as well as in state structures. In the world, infrastructure for 5G technology is provided by only a few manufacturers. In Europe, Nokia and Ericsson, and outside Europe, Chinese Huawei and ZTE and Korean Samsung. In the last few years, the issue of supplying equipment for the construction of 5G infrastructure from China has become the subject of a heated discussion between the US and China. From the US side, doubts are raised as to whether this equipment ensures the security of use of 5G services by citizens and entities around the world, including those in the European Union (“EU”), due to the possible influence on their manufacturers by the Chinese government. The discussion between the US and China resulted in the adoption of a number of recommendations in the EU in the field of 5G cybersecurity, including Cybersecurity of 5G networks EU Toolbox of risk mitigating measures (“5G Toolbox”). Specific recommendations have been formulated in the 5G Toolbox regarding the so-called High Risk Vendors (“HRV”). Based on these recommendations, some EU countries have introduced national regulations regarding HRV. Due to the different pace of adoption of these regulations in individual EU countries and the different ways of implementing these regulations and enforcing already implemented provisions, demands are being made to adopt a uniform regulation in the EU in the field of HRV, which would apply to all EU countries. The article analyzes whether it is justified to adopt uniform EU regulations in this regard at the current stage of the adopted regulations regarding HRV.